On Some Problems of Commercial Law in Ukraine - Oleksandr Romanovich Kovalyshyn (Societas et Iurisprudentia, 2021)
The paper is devoted to the disclosure of certain aspects of recodification in Ukraine, some existing problems of the Ukrainian commercial law as well as the conflict of norms between the Commercial Code of Ukraine and the Civil Code of Ukraine. In year 2020, the Concept of Civil Legislation Reform was adopted in Ukraine. The Concept of Civil Legislation Reform states that the systematic renewal of the Civil Code of Ukraine as a whole is possible only if the Commercial Code of Ukraine is repealed because the latter does not meet the parameters of the acts governing business relations which, by their nature, are primarily private. The presented study explains the current problems of the Ukrainian commercial law as well as civil law regulation of business relations for both: 1) the foreign scholars dealing with the civil law and commercial law; 2) the foreign investors (including investors from the European Union countries) who are already conducting economic activities in Ukraine or plan to invest in the Ukrainian economy. Special attention is given to such issues like the types of ownership, penalties for obligations, differences in legal capacity, difference of approaches to the system of legal entities, existence of some archaic legal forms of entrepreneurial activity, etc. The author emphasizes that undoubtedly the Commercial Code of Ukraine as well as the Civil Code of Ukraine need some updating. There is an urgent need to systematize the existing organizational and legal forms of legal entities and to renew the basics of civil law regulation in Ukraine. It is explained in the paper, while in most neighbouring jurisdictions steps are being taken to systematic update of the commercial codes (including expanding the scope of their legal regulations), in Ukraine steps are being taken to eliminate the commercial code. This seems completely unacceptable; it harms the legal regulation of business relations in Ukraine significantly and slows down the progressive development of the Ukraine’s economy. The analysis of the commercial codes abroad shows that there is no single approach to the list of legal constructions that should form the basis of the relevant code. All, without exception, codified acts of this type are characterized by the presence of special institutions that, from the point of foreign lawyer’s view or current trends in private law, may seem do not meet certain standards.